Altered B-Lymphocyte Homeostasis in Idiopathic Nephrotic Syndrome - Ling, Chen; Wang, Xiaolin; Chen, Zhi; Fan, Jianfeng; Meng, Qun; Zhou, Nan; Sun, Qiang; Hua, Lin; Gui, Jingang; Liu, Xiaorong (Frontiers in Pediatrics, 2019)
B-cell-deleted therapy has been successfully used for children with idiopathic nephrotic syndrome (INS), suggesting that B cells may be involved in the pathogenesis of INS. However, few studies have focused on the alteration of B-cell homeostasis in INS. Methods We measured the levels of B-cell subsets in the blood of 87 INS children, prior to the application of steroids, by flow cytometry. INS patients were divided into steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS) groups based on their sensitivity to steroids after a one-month follow-up. Subsequently, we compared these INS patients with age- and sex-matched patients with recurrences (n = 37) and remissions (n = 32), as well as healthy controls (n = 75). Results We found that 65 SSNS patients exhibited an altered peripheral-blood B-cell-subset distribution, with increased levels of total, transitional, memory, IgM (immunolobulin M) memory and switched-memory B cells compared to 22 SRNS patients. In contrast, the levels of B-cell subsets in SRNS patients were generally the same as those in remission patients and healthy controls. Patients in relapse presented elevated memory B cells compared to those in other groups. The area under the ROC (receiver operating characteristic) curve of transition B cells at initial onset for the prediction of SSNS was 0.907 (95% confidence interval, 0.835–0.979). The analysis rendered an optimal cut-off value of 2.05 (% Lymphocyte) corresponding to 79.1% sensitivity and 90.9% specificity. The percentages of total B cells (P = 0.013, R = −0.278), memory B cells (P = 0.001, R = −0.354) and switched-memory B cells (P = 0.004, R = −0.320) were negatively correlated with the level of serum albumin during the active stage of the disease. Conclusions We observed and verified that B-cell subsets are significantly altered in children with SSNS. We propose that elevated transitional B cells may be a promising marker for predicting successful immunosuppressive therapy during the initial onset of INS. Memory B cells contribute to low serum albumin and further research is needed to determine the function of memory B cells in INS.